High‐Resolution Single‐Molecule Fluorescence Imaging of Zeolite Aggregates within Real‐Life Fluid Catalytic Cracking Particles1. Issue 6 (12th December 2014) - Ristanović, Zoran; Kerssens, Marleen M.; Kubarev, Alexey V.; Hendriks, Frank C.; Dedecker, Peter; Hofkens, Johan; Roeffaers, Maarten B. J.; Weckhuysen, Bert M.
Abstract: Fluid catalytic cracking (FCC) is a major process in oil refineries to produce gasoline and base chemicals from crude oil fractions. The spatial distribution and acidity of zeolite aggregates embedded within the 50–150 μm‐sized FCC spheres heavily influence their catalytic performance. Single‐molecule fluorescence‐based imaging methods, namely nanometer accuracy by stochastic chemical reactions (NASCA) and super‐resolution optical fluctuation imaging (SOFI) were used to study the catalytic activity of sub‐micrometer zeolite ZSM‐5 domains within real‐life FCC catalyst particles. The formation of fluorescent product molecules taking place at Brønsted acid sites was monitored with single turnover sensitivity and high spatiotemporal resolution, providing detailed insight in dispersion and catalytic activity of zeolite ZSM‐5 aggregates. The results point towards substantial differences in turnover frequencies between the zeolite aggregates, revealing significant intraparticle heterogeneities in Brønsted reactivity. Abstract : Real‐life fluid catalytic cracking (FCC) catalyst particles have been studied with a combination of single‐molecule fluorescence nanoscopy and stochastic optical fluctuation imaging methods. Zeolite ZSM‐5 aggregates and their reactivity could be mapped with unprecedented spatiotemporal resolution and sensitivity, revealing significant differences in turnover frequencies of the embedded individual zeolite particulates.